Their satanic majesties' movies: The Rolling Stones in cinema. (1st December 2016) - James, David E.
From the mid-1950s to the early-1970s, the several phases of the rock 'n' roll film differently negotiated the various kinds of delinquency attributed to the new music. At its inception, critics associated what was thought to be its musical delinquency with social delinquencies: working-class and African American's insubordination, and sexual promiscuity. The 1950s' jukebox musicals, the first rock 'n' roll film genre, disputed these associations and narrated the music as innocuous teenage entertainment, fully compatible with and assimilable to the culture industries. Documentary films about late-1960s' 'rock', most notably Monterey Pop (D. A. Pennebaker, 1968) and Woodstock (Michael Wadleigh, 1970), transvalued the terms of the earlier critiques and celebrated their role in a biracial folk community based on peace and love. Films about the Rolling Stones, however, re-asserted the delinquencies, affirming instead the band's associations with violence, misogyny and insurrection. The most crucial of them, Gimme Shelter (Albert and David Maysles and Charlotte Zwerin, 1970), portrayed the collapse of the utopian countercultural community earlier films had proposed.